The ethics of Japan's global environmental policy the conflict between principles and practice - Kagawa-Fox, Midori (Routledge contemporary Japan series, 2012)
"This work examines Japanese government policies that impact on the environment in order to determine whether they incorporate a sufficient ethical substance. In the enquiry into the ethics of the policies, Kagawa-Fox explores how Western philosophers combined their theories to develop a 'Western environmental ethics code'; she also reveals the existence of a unique 'Japanese environmental ethics code' built on Japan's cultural traditions, religious practices, and empirical experiences. The discovery of the distinctive Japanese code is not only important for what it discloses as a new philosophy, but most importantly how it can be used to analyse the ethical framework of the Japanese policies. In spite of the positive contributions that Japan has shown towards the global environment, the government has failed to show a corresponding moral obligation to the world ecology in its global environmental policy. The policies examined in the three case studies comprising whaling, nuclear energy, and forestry, have also been found wanting in ecological ethical considerations, both from a Western and Japanese perspective. The main reason for this is that the integrity of the policies has been compromised by Japanese vested interest groups; business and political interests ensure that the policies are primarily focused on maintaining sustainable economic growth. Whilst Japan's global environmental policy initiatives are the key to its economic survival into the 21st century, and these initiatives may achieve their aim, they do however fail the Japanese code of environmental ethics."--Publisher's description.